Social Deviation Of Gambling Behavior And Its Impact On Family Harmony - Rian Fadilah (Feelings: Journal of Counseling and Psychology, 2025)
Online gambling behavior is a form of social deviation and its impact on family harmony. Gambling behavior has become a social issue that attracts attention in modern society because of its potential negative impacts on individuals and families. This phenomenon causes challenges in dealing with its social impacts in an era of technological advancement and easy access to gambling. Some factors that influence gambling behavior include life pressure and stress, the influence of the social environment, and a lack of understanding of negative consequences. This study shows that gambling behavior can cause conflict in the family, financial problems, and disruption of relationships with the surrounding environment.